Dampak Zakat Produktif dalam Penguatan Modal dan Kinerja UMKM pada Kelompok Usaha Mandiri di BAZNAS Provinsi NTB - Basit, Abdul; Rosidayanti, Rosidayanti (WELFARE Jurnal Ilmu Ekonomi, 2020)
This study aims to determine the impact of productive zakat distribution in strengthening the capital and performance of Micro Small and Medium Entreprises. The Micro Small and Medium Entreprises referred to the members of the independent business group in the National Zakat Agency (BAZNAS) in West Nusa Tenggara Province (NTB). The approach used in this research is a qualitative approach with a case study strategy. The data collection technique uses observation, interview and direct documentation to the object concerned. The data validity technique used triangulation. The results of this study indicate that the practice of distributing zakat for productive activities and businesses provided by the National Zakat Agency (BAZNAS) can improve the capital structure, so that it has an impact on capital strengthening. In addition, the assistance or training provided by BAZNAS in NTB Province has an impact on improved business performance being managed. The final impact is an increase in business income managed by mustahik, so as to create independence and welfare for MSME players.Â Penelitian ini bertujuan untuk mengetahui bagaimana dampak dari praktik penyaluran zakat secara produktif terhadap penguatan modal dan kinerja UMKM pada Kelompok Usaha Mandiri di Badan Amil Zakat Nasional (BAZNAS) Provinsi Nusa Tenggara Barat (NTB). Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan strategi studi kasus. Teknik pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi langsung kepada objek yang bersangkutan. Teknik keabsahan data menggunakan triangulasi. Hasil penelitian ini menunjukkan bahwa dari praktik penyaluran zakat untuk kegiatan dan usaha produktif yang diberikan oleh Badan Amil Zakat Nasional (BAZNAS) dapat meningkatkan struktur modal, sehingga berdampak kepada penguatan modal, selain itu, pendampingan atau pelatihan yang diberikan oleh BAZNAS di Provinsi NTB berdampak pada meningkatnya kinerja usaha yang dikelola. Dampak akhir yang dirasakan yaitu terjadinya peningkatan pendapatan usaha yang dikelola mustahik, sehingga tercipta kemandirian dan kesejahteraan para pelaku UMKM.